2007 GUIDELINES FOR THE MANAGEMENT OF ARTERIAL HYPERTENSION (ENDING) (Столичная издательская компания, 2016)
The Task Force for the Management of Arterial Hypertension of the European Society of Hypertension and of the European Society of Cardiology.